2021
DOI: 10.4103/ajop.ajop_32_21
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-D status among Egyptian children and adolescents

Abstract: Background and aim Vitamin D is essential for growth, development, and health. It works as a paracrine and autocrine signaling molecule that affects nearly all systems in the body. Vitamin-D deficiency (VDD) may be overlooked due to the variable clinical presentations. This study was conducted to assess vitamin-D status among children and adolescents, and to find out predictors for its deficiency/insufficiency among the studied groups. Patients and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…But a different small study based on a population of Egyptians found a significant frequency of VDD (60.9%) and VDI (17.7) (16) . Which did not concur with our findings.…”
Section: Discussionmentioning
confidence: 86%
“…But a different small study based on a population of Egyptians found a significant frequency of VDD (60.9%) and VDI (17.7) (16) . Which did not concur with our findings.…”
Section: Discussionmentioning
confidence: 86%